Structural Evolution of Anatase‐Supported Platinum Nanoclusters into a Platinum‐Titanium Intermetallic Containing Platinum Single Atoms for Enhanced Catalytic CO Oxidation. Issue 2 (7th December 2022) - He, Wenxue; Zhang, Xu; Zheng, Kun; Wu, Chuanqiang; Pan, Ya; Li, Hongmei; Xu, Liuxin; Xu, Ruichao; Chen, Wei; Liu, Yi; Wang, Chao; Sun, Zhihu; et al.
Abstract: Strong metal‐support interactions characteristic of the encapsulation of metal particles by oxide overlayers have been widely observed on large metal nanoparticles, but scarcely occur on small nanoclusters (<2 nm) for which the metal‐support interactions remain elusive. Herein, we study the structural evolution of Pt nanoclusters (1.5 nm) supported on anatase TiO2 upon high‐temperature H2 reduction. The Pt nanoclusters start to partially evolve into a CsCl‐type PtTi intermetallic compound when the reduction temperature reaches 400 °C. Upon 700 °C reduction, the PtTi nanoparticles are exclusively formed and grow epitaxially along the TiO2 (101) crystal faces. The thermodynamics of the formation of PtTi via migration of reduced Ti atoms into Pt cluster is unraveled by theoretical calculations. The thermally stable PtTi intermetallic compound, with single‐atom Pt isolated by Ti, exhibits enhanced catalytic activity and promoted catalytic durability for CO oxidation. Abstract : Pt clusters of 1.5 nm supported on anatase TiO2 transform exclusively into CsCl‐type PtTi intermetallic compound particles that grow epitaxially along the TiO2 (101) planes after H2 reduction at 700 °C. The formation of PtTi occurs through migration of reduced metallic Ti atoms into Pt clusters. The thermally stable PtTi intermetallic exhibits enhanced catalytic activity and promoted catalytic durability for CO oxidation.